Between the temptations of privatizing and globalizing religion - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2014)
In this article, I analyse two mutually exclusive contemporary temptations in Christianity, that is, the temptation to treat religion as private and the temptation to treat it as global. Both temptations have determinants that can be found inside as well as outside religion. They are also determined by general tendencies present in Western culture. The discussed temptations as well as their determinants can be explained by the functional analysis postulated by the Weberians and performed by me in this paper. The analysis, applied here to two selected cases of catholic priests, Father Lemański and Father Natanek, allows us to explain why their speeches are not and will not be accepted by the Church’s authorities.
Keywords: Christianity; religion